Serum endocan and endothelial dysfunction in childhood acute lymphoblastic leukemia survivors: a tertiary center experience - Laila M. Sherief; Elhamy R. Abd El-khalek; Ibrahim A. Libda; Osama A. Gaber; Naglaa M. Kamal; Basma K. Soliman; Wesam A. Mokhtar; Ghada A. Mokhtar; Hosam E. Salah; Gehad M. Kamar; Marwa Zakaria (SAGE Publishing, 2021)
Background: An increased risk of cardiovascular complications is reported in survivors of childhood acute lymphoblastic leukemia (ALL). Early identification of impaired vascular health may allow for early interventions to improve outcomes. Aim: The study was conducted to assess the endothelial dysfunction in ALL survivors using a new marker, serum endocan, and measurement of the mean common carotid arteries intima media thickness (cIMT). Methods: A case-control study was conducted on 100 childhood ALL survivors (aged 6-18 years), with 80 healthy age and sex-matched children as a control group. Lipid profile, hepatitis markers, and serum ferritin where measured, in addition to the measurement of serum endocan. and cIMT by B-mode high-resolution ultrasonography for all study participants. Results: Triglycerides, total cholesterol, post prandial glucose, and serum ferritin were significantly higher in ALL survivors than controls ( p  < 0.05). Dyslipidemia was detected in 6% of ALL survivors. ALL survivors showed statistically higher serum endocan levels (470.41 ± 556.1 ng/l, versus , 225.94 ± 185.2 ng/l, respectively) and increased cIMT levels compared with the control group (0.650 ± 0.129 mm versus 0.320 ± 0.095 mm, respectively) p  < 0.05. Serum endocan was positively correlated with cIMT and blood cholesterol. Conclusions: The survivors of childhood ALL demonstrated an elevated level of serum endocan and increased cIMT. These can be used as predictors of endothelial dysfunction, and, as a consequence, the risk of developing premature atherosclerosis.